Cuidados com a saúde infantil em famílias de imigrantes em tempos de pandemia da Covid-19 - Coimbra, Eliana Gonçalves (2023)
Immigration is a demographic phenomenon that was spurred during the COVID-19 pandemic, an event that has transformed social relations and required a global level of care with deep fissures between populations, especially among the most vulnerable segments. The situation of immigrant families is traversed by a process of socioeconomic inequalities and inequalities in access to health care. In the context of the pandemic, the continuity of care for children, especially immigrant children, has shown difficulties in the search for promotion and prevention services, both on the part of families and in the provision by health professionals and services. The main objective of this research was to understand the organization of health care for families and children in times of pandemic, from the perspective of immigrants. An exploratory and qualitative study was conducted with 15 immigrant families interviewed in the municipality of Foz do Iguaçu, Brazil, between May and December 2022. Data were analyzed using Meaning Interpretation. Participants described their choice of Brazil as being due to the possibility of a smooth entry, as Brazilian borders were open; the perception that it is a country with a welcoming attitude; the fact that it has inclusive public health and social assistance policies; an agile legal framework that facilitates documentary procedures; and work and education opportunities. Although the pandemic has required changes in family and social organization, the perception of danger and the real fear of death have been overcome by an understanding of the importance of virus prevention and containment strategies, vaccination, protection and family health care. Health care for children experienced by families during this period included medical consultations, vaccination, dental services, and purchase of medications and vitamins. In terms of care, a wide coverage of Brazilian health services was observed, as well as a welcoming and humanized treatment, while situations of slowness in care, differences for being an immigrant, impatience to understand the language, lack of trust and receptivity were listed. The possibility of access to the Unified Health System and the potential of Brazilian services permeated the different experiences of the families, even when the care was disrespectful to their culture, management and popular care. Hence, for immigrant families, Brazil's welcoming attitude and the scope of social assistance meant ease in obtaining documentation, employment opportunities, access to health and education, even if this required changes in the way of being and living day to day. Thus, although Brazil has a universal health system, it is necessary to ensure that access occurs without distinction or trivialization of the immigrant's own characteristics.